Analisis Interaksi Sosial Mahasiswa Pengguna Aplikasi Instagram Pada Mahasiswa MPI Stambuk 21 - Eka Susanti; Fella Annisa Harahap; Yuni Syafriani (Pusat Riset dan Inovasi Nasional, 2025)
Technological advances have led humans to create new forms of interacting and socializing, one of which is communication technology innovation in the form of social media. With the rapid development of new media, it has had an impact on communication sites, from just email and chat, to social media or social networks. One of the social media that is currently widely used by gadget users is Instagram. The aim of this research is to find out the role of Instagram social media in social interaction between students in the Islamic Education Management Department of Stambuk 21 and to find out how students at the Faculty of Tarbiyah and Teacher Training, North Sumatra State Islamic University behave in using Instagram social media. Researchers used purposive sampling to determine research informants, while data collection techniques used interviews and documentation. The analysis process includes data reduction, data presentation and drawing conclusions. The results of this research show that the social media Instagram plays an important role in social interaction between students at the Faculty of Tarbiyah and Teacher Training, UIN North Sumatra.